Scaling industrial carbon dioxide removal: Policy options for a short-term strategy - Felix Schenuit; Domenik Treß (Stiftung Wissenschaft und Politik (SWP), 2025)
The role of permanent carbon dioxide removal (CDR) from the atmosphere is currently the subject of intensive discussion within the context of developing a new EU emissions reduction target for 2040 and a German long-term strategy on negative emissions. At the same time, a short-term strategy for the coming years is needed to ensure the successful scaling of technologies for what can be called "industrial CDR". So far, the focus has tended to be on a conceptual discussion of the quantities of CDR that are required to achieve net-zero greenhouse gas emissions; as a result, sufficient attention has not been paid to the question of how and on what time horizon the first large-scale CDR projects can come into being. Some countries have already developed short-term instruments aimed at triggering an initial investment drive into industrial CDR. A comparative assessment of these approaches reveals several viable policy options for targeted CDR scaling in both the EU and Germany.
Keywords: 320; carbon dioxide removal (CDR); new EU emissions reduction target for 2040; German long-term strategy on negative emissions; carbon dioxide; EU Emissions Trading System (ETS); land use; land-use change and forestry (LULUCF)